Examining the Factors Affecting the Use of Crypto Assets as Foreign Payment and Investment Instruments: A Quantitative Study - Güneş Yılmaz; Tayfur Süleyman Koç (İzmir İktisat Dergisi)
The aim of the study is to examine the factors affecting individuals' intentions to use crypto assets as foreign payment and investment instruments. A research model based on the UTAUT-2, a widely accepted model that examines individuals' attitudes toward information technologies, was formed, and the factors affecting two dependent variables, "intention to use in foreign payments" and "intention to invest," were analyzed with PLS-SEM. Path coefficients (β) demonstrated that the variables significantly affecting the intention to use in foreign payments were "performance expectancy," "social influence," and "perceived risk," respectively. Moreover, in order of importance, "performance expectancy," "social influence," "awareness," and "perceived risk" were determined as the variables significantly affecting the intention to invest. Along with path coefficients, f² and q² effect sizes were also analyzed to examine the interaction between the variables. In the context of empirical findings, it was evaluated that the most significant factors in the participants' tendency to use crypto assets in foreign payments and investment transactions were "performance expectancy" and "social influence”. Contrary to the widespread approach in the literature, the study has revealed crucial results for the literature and future studies by addressing the two main financial functions of crypto assets and the factors significantly affecting these functions.